The Relevance of the European Consumer Protection Law for the Development of the European Contract Law - Schurr, Francesco A (Victoria University of Wellington Law Review, 2007)
This paper deals with the interaction of consumer law and contract law in the European Union. Over the last two decades the European legislature has adopted many legislative measures in the field of consumer protection that were designed to strengthen the single market and to avoid distortion of competition. Thus the European legislature tried to approximate or harmonise consumer protection standards within the European Community and consequently created a new layer of supranational contract law which now coexists with the traditional national contract law regimes. The paper assesses the various types of contract law on the international, supranational and national levels and discusses the problems arising from the fact that the contract law in the European Community is so diverse. Directive 2005/29/EC on Unfair Business-to-Consumer Commercial Practices is discussed as a very prominent recent product of European Community consumer legislation. The paper points out how the development of European consumer law serves as a catalyst for the further development of a genuine European contract law.